In Fascination of Fluid Dynamics A Symposium in Honour of Leen van Wijngaarden - Biesheuvel, Arie; Heijst, Gertjan F. van (Fluid Mechanics and its Applications, 1998)
In Fascination of Fluid Dynamics contains a collection of papers by international experts in hydrodynamics, based on oral presentations at a symposium held in honour of Professor Leen van Wijngaarden on his 65th birthday. The book begins with a personal sketch of his life and scientific career. It continues with a mixture of papers that address recent developments in various branches of fluid mechanics. Many of the papers cover different aspects of multiphase flows: bubble dynamics, cavitation, bubbles and particles in turbulent flows, suspension flows, and wave phenomena in fluidised beds. Other topics that are addressed include: dynamics of jets, shock waves, MHD turbulence, selforganisation phenomena in 2D turbulence, vortex rings and the thermodynamics of tropical cyclones. This edited volume will be valuable reading for researchers, engineers and students interested in hydrodynamics, and in particular in multiphase flows